PENGARUH KESADARAN MEREK DAN PERSESPSI KUALITAS TERHADAP LOYALITAS MEREK MELALUI KEPERCAYAAN MEREK SEBAGAI VARIABEL INTERVENING PADA PONSEL NOKIA ( Studi pada mahasiswa Fakultas Ilmu Sosial dan Ilmu Politik Universitas Diponegoro ) - Anita Dwi Kurniati; Naili Farida; Sendhang Nurseto (Jurnal Ilmu Administrasi Bisnis, 2013)
This study aims to determine the effect of brand awareness and perceived quality of the Nokia brand loyalty through brand trust as an intervening variable. The sample used by 100 respondents using Simple Random Sampling technique. The method of analysis used in this study is the Path analysis. the calculation results showed that the variables of brand awareness, perceived quality variables, and variable keperayaan each brand has a positive and significant effect on the variable of brand loyalty. Influence exerted by the awareness of the brand loyalty variable that is equal to 12.2%, and the variable perceived quality of the brand loyalty of 28%. Variables brand awareness, perceived quality variables, and the variables are combined brand trust has a positive and significant effect on the variable of brand loyalty at 69.1%, while the remaining 30.9% is explained by other factors, variable brand image, brand association variable, and variations in price promotions. Based on calculations Path analysis proved that the variable brand trust as an intervening variable can be a mediator reinforcing relationship between perceived quality variables with the variables of brand loyalty. Meanwhile variable became brand trust mediator variable relationship weakens brand awareness to brand loyalty variable. Suggestions of this research is to improve the quality of the product, adding features, the company maintaining long term relationships with its customers objective that consumers remain loyal to the Nokia brand phones.